Patrick Chamoiseau et le Gwo-Ka du chanté-parlé - Pim Higginson (Studies in 20th & 21st Century Literature, 2004)
Numerous critics have explored the use of orality in Patrick Chamoiseau's work. Solibo Magnificent adds to the opposition between the oral and the written the third term of the musical. Western artistic expression maintains a neat border between the media (e.g. literature, music, the plastic arts) because it helps legitimate the essentialization of (racial, ethnic, sexual) alterity: white maleness writes; the musical is instead associated with otherness (and orality). This hinged or articulated connection between alterity and the musical (and sameness and the literary) assures and assumes that the musical does not signify. This essay contends that Chamoiseau's novel responds to (and undermines) the West's regimentation of the relationship between the musical and the literary by showing another possible relationship between the two media—one in which their radical opposition is abolished. In this alternate conception of expression, language becomes rhythmic and melodic—offers an aural-sensory experience that the West associates with the musical—just as music wanders into the forbidden territory of signification. The resulting novel is not simply another mode of expressive being but a critical examination of the categories of the literary and musical themselves as strategically situated participants in a historical process of Western authorial and authoritarian domination.
Keywords: Patrick Chamoiseau; orality; Solibo Magnificent; written; musical; Western artistic expression; literature; music; plastic arts; media; racial; ethnic; sexual; white maleness; otherness; alterity; sameness; radical opposition; aural-sensory experience; authorial domination; authoritarian domination